SELECTIVE OESTROGEN RECEPTOR MODULATORS DIFFERENTIALLY POTENTIATE BRAIN MITOCHONDRIAL FUNCTION - Irwin, Ronald W. (2012)
The mitochondrial energy-transducing capacity of the brain is important for long-term neurological health and is influenced by endocrine hormone responsiveness. This study aimed to determine the role of oestrogen receptor (ER) subtypes in regulating mitochondrial function using selective agonists for ERα (PPT) and ERβ (DPN). Ovariectomised female rats were treated with 17β-oestradiol (E2), PPT, DPN or vehicle control. Both ER selective agonists significantly increased the mitochondrial respiratory control ratio and cytochrome oxidase (COX) activity relative to vehicle. Western blots of purified whole brain mitochondria detected ERα and to a greater extent, ERβ localization. Pre-treatment with DPN, an ERβ agonist, significantly increased ERβ association with mitochondria. In hippocampus, DPN activated mitochondrial DNA-encoded COXI expression whereas PPT was ineffective indicating that mechanistically ERβ, not ERα, activated mitochondrial transcriptional machinery. Both selective ER agonists increased protein expression of nuclear DNA-encoded COXIV suggesting that activation of ERβ or ERα is sufficient. Selective ER agonists up-regulated a panel of bioenergetic enzymes and antioxidant defense proteins. Up-regulated proteins included pyruvate dehydrogenase, ATP synthase, manganese superoxide dismutase, and peroxiredoxin V. In vitro, whole cell metabolism was assessed in live primary cultured hippocampal neurons and mixed glia. Results of in vitro analyses were consistent with in vivo data. Further, lipid peroxides, accumulated as a result of hormone deprivation, were significantly reduced by E2, PPT, and DPN. These findings suggest that activation of both ERα and ERβ are differentially required to potentiate mitochondrial function in brain. As active components in hormone therapy, synthetically designed oestrogens as well as natural phyto-oestrogen cocktails can be tailored to improve brain mitochondrial endpoints.